2002
DOI: 10.1007/s00280-002-0487-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical adjuvant chemotherapy for superficial transitional cell bladder carcinoma: results of a randomized trial with epirubicin comparing short-term versus long-term maintenance treatment

Abstract: This analysis indicated that extended prophylactic maintenance instillation of EPI was not significantly effective in reducing bladder cancer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…However, in another study comparing 11 instillations of epirubicin during 12 mo to 9 instillations during 6 mo, no difference was found [18]. Likewise, no difference was found in a study comparing 19 instillations of epirubicin during 12 mo to 12 instillations during 5 mo [21]. In all three of these trials there is a possible dilution of the size of the treatment effect due to recurrences in the long-term treatment arm prior to starting the long-term instillations at 5 or 6 mo.…”
Section: If One Immediate Instillation Is Not Given How Long Should mentioning
confidence: 92%
See 1 more Smart Citation
“…However, in another study comparing 11 instillations of epirubicin during 12 mo to 9 instillations during 6 mo, no difference was found [18]. Likewise, no difference was found in a study comparing 19 instillations of epirubicin during 12 mo to 12 instillations during 5 mo [21]. In all three of these trials there is a possible dilution of the size of the treatment effect due to recurrences in the long-term treatment arm prior to starting the long-term instillations at 5 or 6 mo.…”
Section: If One Immediate Instillation Is Not Given How Long Should mentioning
confidence: 92%
“…One year of chemotherapy-Three trials using various drugs compared short-term instillations of 5-6 mo to instillations during 1 yr [13,18,21]. In one study, fewer patients had recurrence with 12 mo of MMC or Adriamycin (15 instillations) as compared to 6 mo of treatment (9 instillations), 41.2% versus 55.8% (p = 0.01) [13].…”
Section: If One Immediate Instillation Is Not Given How Long Should mentioning
confidence: 99%
“…The dwell time was at least 1 h in 9 studies. However, 4 studies [17,25,30,31] did not describe the details of dwell time.…”
Section: Study Characteristicsmentioning
confidence: 96%
“…Among these studies, two trials [17,33] were simple randomization, four trials [11,25,31,32] were stratified randomization and a dynamic method was used in the trial by Kuroda in 2004 [29] . Other five trials [21,24,26,27,30] only described "randomly assigned" without sufficient information for judgment, so were evaluated as "unclear". The patients in the last trial by Hendricksen in 2008 [28] were allocated according to the date of TURBT, so was judged as "high risk of bias".…”
Section: Risk Of Bias In Included Studies 231 Allocation (Selectionmentioning
confidence: 99%
“…This adjuvant does not specifically target the disease. It has also been shown that intravesical chemotherapy could be effective in decreasing the short-term incidence of tumour recurrence (1,7). No evidence was found however that such treatment could decrease the long-term incidence of tumor recurrence, according to 60-to 77-month follow-up study (1).…”
Section: Introductionmentioning
confidence: 99%